Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Sentra Industri Rajut Binong Jati Bandung. - Luthfia Elsyifa (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2020)
This study aims to see how compensation and work motivation influence employee performance. The research was conducted at the Industrial Center for Knitting Binong Jati Bandung. The research method used is descriptive and verification. Data interview techniques used were observation, interviews and questionnaires to 93 respondents. The data analysis method used is linear regression, multiple descriptions, and coefficient of determination. The results of this study indicate that compensation and work motivation have a positive and significant effect on employee performance. Compensation and work motivation have an effect on employee performance by 56.90%, the dominant independent influence variable is work motivation by 29.3%, while compensation is 27.6%.